The Controversy over the Term ‘The Third Pentecost’: Bhinneka Tunggal Ika Perspective - Philip Suciadi Chia, D.Th, Ph.D; Pontas Surya Fernandes; Urbanu Da Costa; Endemina Ivamut; Daniel Rumaikewi (Pharos Journal of Theology)
A well-known Indonesian pastor, Niko Njotorahardjo has popularized the term the ‘third Pentecost’. This term is motivated by his belief that the outpouring of the Holy Spirit occurs in this age to fulfill the Great Commission before the second coming of Jesus Christ. Pastor Njotorahardjo preaches the calling of the third Pentecost to the whole world including for example Europe, Hansei University in South Korea, Israel, and Oral Roberts University in Oklahoma. Co-founder of Generals International Ministry, Cindy Jacobs, welcomes the calling of the ‘third Pentecost’, saying, “pastor Niko Njotorahardjo is indeed the messenger of the third Pentecost.” French L. Arrington, a Biblical scholar at Pentecostal Theological Seminary, also endorses the calling of the third Pentecost, stating that pastor Niko Njotorahardjo might be right on the ‘third Pentecost’. Despite these acceptances, the notion of the third Pentecost still receives criticism in Indonesia. Abraham (2019: 17-28) and Simanjuntak (2019: 147-156), for instance, question the term of the ‘third Pentecost’ because there is only one Pentecost according to them, and it occurs in the book of Acts. This article, attempts to respond to the issue of the third Pentecost in light of Bhinneka Tunggal Ika. It suggests that there should be peaceful discussions relating to the idea of a third Pentecost which is problematic for many believers and that Bhinneka Tunggal Ika (unity in diversity) should be used as its methodology because it offers a constructive dialogue approach to the highly debated term: the ‘third Pentecost’. Thus, this article advocates for the application of Bhinneka Tunggal Ika (unity in diversity) as a methodological framework, as it facilitates a productive dialogue regarding the contentious term: the ‘third Pentecost’. This principle encourages the acceptance of differences and disagreements while fostering a spirit of unity. Consequently, Christians can express their diverse views in a more respectful and charitable manner.